1- Purpose, Human Sociality and Nature in Akiwowo’s Sociology of Knowledge: A Realist Interpretation. - Ademoyo, Adeolu (African Sociological Review, 2009)
This paper advances the view that there is an ontological commitment in Akiwowo’s sociology of knowledge which offers an exposition of his thought on purpose, human sociality, nature and society. The paper defends a realist interpretation of this ontology. It argues that a realist interpretation of Akiwowo’s account of human sociality, nature and society shows two major conclusions.One, social actions in society are human actions. Human actions are not isolated atoms. Therefore social actions are linked by the agency and, subjectivity of the human which is imbued with values and her/his capacity of sociality. Two, a condition for the continuous existence of a society is that such society has goals. The evidence for this is simple: we see it. This view of society differs from the traditional view of purposiveness in society. The paper suggests that these two conclusions show Akiwowo’s theoretical distance from positivism. This rejection of positivism moves him closer to a natural law position.